Issues of Regulating Economic Agents Behavior in Territorial Development Management - M. M. Nizamutdinov; V. V. Oreshnikov (Управленческие науки, 2018)
One of the key problems in managing the development of territorial socio-economic systems is inconsistency and contradictory interests of various economic agents. In modern conditions, it is impossible to avoid the need to reconcile interests, even when one of the parties is the subject of management. The article examines the process of regulating behavior of economic agents in the system of strategic management of territorial development. The procedures of decision-making and the influence of various factors on them, including regulators are analyzed. Developing of an approach to managing the behavior of economic agents in the territorial socio-economic system based on the interests of not only management systems, but also the economic agents themselves.Methodology. The research is based on the principles of system and complexity, factor analysis, comparative analysis, grouping methods, economic and mathematical modeling, elements of set theory and fuzzy logic are also used.The general methodical scheme of behavior management of economic agents at the regional level, characterized by the presence of an iterative procedure of differential impact on the factors and deterministic properties of the behavior of agents with a mechanism for assessing the degree of influence of regulatory actions based on feedback, is proposed. The developed approach allows to form within the framework of market mechanisms, the target scenario of the behavior of economic agents in the process of developing a coherent strategy for the development of the regional socio-economic system.The development and adoption of managerial decisions should be based on taking into account the interests of all stakeholders. Therefore, this role of public authorities also includes the definition of regulators, allowing adjusting and coordinating the behavior of other economic agents. It is also should be mentioned that management bodies can also act as interacting agents. Accordingly, local self-government bodies act not only in the role of an element of management system, but also in the role of a legally independent counterparty when interacting with the governing bodies of a constituent entity of the Russian federation.